THE ROLE OF ORGANIZATIONAL CLIMATE IN IMPROVING JOB SATISFACTION - Dewi Suma; Budi Alamsyah Siregar (Institute of Computer Science (IOCS), 2022)
This study uses bibliometric analysis and visualization of VOS viewer software to display a graphical conception of bibliographic data, including cocitation and co-occurrence of keywords. The discussion on organizational climate and job satisfaction began to show an increase in the early 2000s until 2018. From early 2020 until now, there has been a decline in the discussion on organizational climate and job satisfaction. The author sees this as an opportunity for new article writers to return to conducting studies and research on organizational climate and job satisfaction. The documents used for analysis in this study were obtained only from the Scopus.com database. This study uses documents published in journals between 1969 and 2022 by building a graphical analysis using the VOS viewer. It is suggested for future research that it is necessary to analyze the journal publications from a wider variety of databases such as JSTOR, Google Scholar, Science Direct, Emerald Insight, and Directory of Open Access Journal widely. This study reports on the significant developments noted by the journal over the years and provides the appropriate information needed for authors writing articles, particularly research in human resource management (HRM). The results of the study present a complete bibliometric analysis and identify the main trends of publication in the Scopus.com journal, especially in the HRD field, data taken from 1969 to 2022.